FISHERIES REGULATION AND ENFORCEMENT IN INDONESIA, MALAYSIA AND THE PHILLIPINES - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Non compliance incidence in the fisheries of Indonesia, Malaysia and the Philippines were found relatively high. The fisheries management is effectively applied when compliance is attained. In order to secure the compliance enforcement and surveillance are needed. In fact, enforcement is costly. This paper suggests adopting the ‘cheap’ enforcement and surveillance strategy using co-management approach.